Impact of Conservation Tillage and Organic Nutrient Sources on Finger Millet Performance in Legume-based Cropping Systems - Narinder Panotra; S. S. Yadav; Lydia Zimik; Vinod Kumar; Lalita Kumar Mohanty; D K Tiwari; Ramya M.; Ram Gopal; Lalit Upadhyay; Ayushi Sharma (Archives of Current Research International, 2025)
This study investigates the impact of conservation tillage and organic nutrient sources on finger millet performance in legume-based cropping systems, highlighting their synergistic effects on soil health, crop yield, and sustainability. Conservation tillage, including no-till and reduced-till practices, helps maintain soil structure, enhance water retention, and reduce erosion. When combined with organic fertilization (such as farmyard manure, vermicompost, and poultry manure), these practices not only improve soil fertility but also increase microbial activity and nutrient cycling. Legume-based intercropping systems, by fixing atmospheric nitrogen, contribute to enhanced soil nitrogen levels, further boosting the growth and yield of finger millet. The study reveals that conservation tillage coupled with organic nutrient sources significantly enhances soil organic matter, microbial diversity, and water-holding capacity. This combination results in improved yields, particularly in legume-based intercropping systems, offering higher total productivity compared to conventional tillage and synthetic fertilization systems. Additionally, the long-term benefits include improved soil carbon sequestration, reduced reliance on synthetic fertilizers, and increased economic sustainability. These practices also support soil biodiversity, contributing to more resilient agricultural systems. The findings suggest that integrating conservation tillage and organic nutrient management can be a sustainable solution for improving finger millet productivity and soil health while ensuring economic viability in the long term. Future research should explore the specific mechanisms through which these practices interact and optimize their implementation for diverse agro-ecological conditions.